2021
DOI: 10.3390/en14217011
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Trapping during Diffusion Generally Observed for Particulate Photocatalytic Films

Abstract: Photo-excited charge carriers play a vital role in photocatalysts and photovoltaics, and their dynamic processes must be understood to improve their efficiencies by controlling them. The photo-excited charge carriers in photocatalytic materials are usually trapped to the defect states in the picosecond time range and are subject to recombination to the nanosecond to microsecond order. When photo-excited charge carrier dynamics are observed via refractive index changes, especially in particulate photocatalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Since holes are scavenged by MeOH, the extension of the response indicates that the recombination process was delayed due to fewer holes available. The decaying process corresponds to the charge carrier trapping to the surface states during diffusion, which has been observed via the refractive index change for various photocatalytic and photovoltaic materials, such as hematite, bismuth vanadate and SrTiO 3 , 24 and it indicates that the observed response was due to the surface-trapped carriers. Overall, it is understood that photo-excited holes were scavenged, causing a longer time for charge carriers to be trapped at the surface states, and, as a result, the recombination of the surface-trapped charge carriers was delayed due to less availability of holes.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Since holes are scavenged by MeOH, the extension of the response indicates that the recombination process was delayed due to fewer holes available. The decaying process corresponds to the charge carrier trapping to the surface states during diffusion, which has been observed via the refractive index change for various photocatalytic and photovoltaic materials, such as hematite, bismuth vanadate and SrTiO 3 , 24 and it indicates that the observed response was due to the surface-trapped carriers. Overall, it is understood that photo-excited holes were scavenged, causing a longer time for charge carriers to be trapped at the surface states, and, as a result, the recombination of the surface-trapped charge carriers was delayed due to less availability of holes.…”
Section: Resultsmentioning
confidence: 89%
“…The information of the charge carriers observed via the refractive index changes is different from those obtained by the conventional time-resolved techniques such as transient absorption and time-resolved photoluminescence methods, and non-radiative charge decay processes such as trapping and interfacial charge transfer have been frequently observed in the photovoltaic and photocatalytic processes. 22–24…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 We also supported the charge trapping during charge diffusion on the nanosecond order for various photovoltaic and photocatalytic materials. 24 Using conventional time-resolved techniques such as timeresolved PL and TA methods, it is difficult to measure the spatial dependence of the charge carrier dynamics, but the microscopic measurements of the TA (and transient reflectivity) and the time-resolved PL could reveal the spatiotemporal behavior of the charge carrier dynamics. 25,26 The TA microscopy showed that the local structure of perovskite domains greatly influenced the charge carrier lifetimes, 27,28 and the charge trapping at sub-bands were visualized, followed by the local heating.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we have developed a new time-resolved microscopic technique called the time-resolved pattern-illumination microscopy (PI-PM) method, where the photo-excited charge carrier dynamics is observed via the refractive index change instead of the absorption change or emission. The detection via the refractive index change is preferred for observation of non-radiative relaxation such as charge diffusion, trapping to the defect/surface states, and interfacial charge transfer. Furthermore, in the analysis of the time-resolved image sequences obtained by the PI-PM method, clustering analysis was used to differentiate the types of charge carriers based on the response time and the signal intensity. ,, …”
Section: Introductionmentioning
confidence: 99%